2019
DOI: 10.1093/femsyr/foz088
|View full text |Cite
|
Sign up to set email alerts
|

Shot-gun proteomics: why thousands of unidentified signals matter

Abstract: Mass spectrometry-based proteomics has become a constitutional part of the multi-omics toolbox in yeast research, advancing fundamental knowledge of molecular processes and guiding decisions in strain and product developmental pipelines. Nevertheless, post-translational protein modifications (PTMs) continue to challenge the field of proteomics. PTMs are not directly encoded in the genome; therefore, they require a sensitive analysis of the proteome itself. In yeast, the relevance of post-translational regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

4
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 104 publications
0
10
0
Order By: Relevance
“…However, as no or minimal differences were observed in the other components of V-ATPase between the MG and control strains, the molecular mechanism leading to the slightly higher abundance of Fba1 in the MG strain remains unclear. Many factors can alter the functionality of proteins, including post-translational modifications, protein localization or interactions with other proteins or biomolecules [80, 81]. A recent study has suggested that phosphorylation regulates the activity of many glycolytic enzymes [7].…”
Section: Discussionmentioning
confidence: 99%
“…However, as no or minimal differences were observed in the other components of V-ATPase between the MG and control strains, the molecular mechanism leading to the slightly higher abundance of Fba1 in the MG strain remains unclear. Many factors can alter the functionality of proteins, including post-translational modifications, protein localization or interactions with other proteins or biomolecules [80, 81]. A recent study has suggested that phosphorylation regulates the activity of many glycolytic enzymes [7].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the number remains very large compared to those resulting from proteomics analysis performed on human cell lines, where at best less than 1% of that number is managed in the initial extract. Post‐translational modifications of proteins can complexify the picture further through the introduction of multiple proteoforms (den Ridder et al, 2020 ). The resulting peptide space is illustrated in Figure 2 .…”
Section: Current Major Challenges In Metaproteomicsmentioning
confidence: 99%
“…Moreover, tools for data mining and interpretation in proteomics may be more complex due to the great variety of signals, such as the possible number of targets for protein modifications and changes in interactions or interactors [217], the variety of analytical approaches [218,219] and of bioinformatics pipelines [220,221], and the associated statistical analyses [222,223], particularly in relation to peptide assembly and subsequent proteome reconstruction. These aspects are crucial to achieve informative and reliable findings, and also taking into account that a great number of fragmentation spectra in a typical shot-gun proteomics experiment remain unidentified and that this large portion of unidentified spectra could originate from unexpected modifications or natural peptide variants [224]. Consequently, proteomics data sharing, starting from raw data to value added information and associated mining tools, would require large investment, infrastructure and coordination [216].…”
Section: Proteomicsmentioning
confidence: 99%